Isolation, Uncertainty and Treatment Delays: Parents' Experiences of Having a Baby with Cleft Lip/Palate During the Covid-19 Pandemic. (January 2023) - Costa, Bruna; McWilliams, Danielle; Blighe, Sabrina; Hudson, Nichola; Hotton, Matthew; Swan, Marc C; Stock, Nicola Marie
Objectives: Previous literature finds that having a child with a cleft lip and/or palate (CL/P) may pose social and emotional challenges for parents. For parents of children born during the Covid-19 pandemic, such challenges may be heightened. Further, novel demands brought about by the pandemic could have caused additional hardships. The aim of this study was to describe the impact of the pandemic on new parents through qualitative exploration of their experiences. Design: Semi-structured interviews were conducted with 14 parents of children born in the United Kingdom with CL/P between January and June 2020, around the start of the pandemic. Data were analysed using inductive thematic analysis. Results: Three themes, with sub-themes, were identified. The first theme, " Changes to Healthcare: The Impact of Restrictions and Reduced Contact", discussed the impact of the pandemic on perinatal care, the care received from the specialist CL/P teams, and parents' experiences of virtual consultations. The second theme, "Family Functioning During the Pandemic", covered parental anxiety, fathers' experiences, and social support. The third theme, " Surgical Prioritisation: Delays and Uncertainty", addressed changes to surgical protocols, coping with uncertainty, complications associated with delayed surgery, and how parents created positive meaning from this period. Conclusions: A range of increased and additional psychosocial impacts for parents were identified, along with several coping strategies, utilization of social support, and the positive aspects of their experiences. As the pandemic continues, close monitoring of families affected by CL/P remains imperative, particularly for those at risk of emotional distress.